2021
DOI: 10.1016/j.jhep.2021.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-induced Hsp90 acetylation is a novel driver of liver sinusoidal endothelial dysfunction and alcohol-related liver disease

Abstract: BackgroundIt is unknown whether liver sinusoidal endothelial cells (LSECs) metabolize alcohol. Chronic alcohol consumption decreases endothelial nitric oxide synthase (eNOS)-derived NO production typical of LSEC dysfunction. Heat shock protein 90 (Hsp90) interacts with eNOS to increase its activity. Cytochrome P450 2E1 (CYP2E1) is a key enzyme in alcohol metabolism and facilitates protein acetylation via acetyl-CoA, but its expression in LSECs is unknown. This study investigates alcohol metabolism by LSECs, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Heat shock protein 90 (Hsp90) activates eNOS, leading to NO production (18). Recently, we reported a mechanism of alcohol-driven LSEC dysfunction (19). In this study, we showed that LSECs can metabolize ethanol and that ethanol can increase Hsp90 acetylation through enhanced production of acetyl-CoA, a substrate for protein acetylation, by the action of alcohol dehydrogenase1 (ADH1) and cytochrome P450 2E1 (CYP2E1) (19).…”
Section: Capillarizationmentioning
confidence: 91%
See 2 more Smart Citations
“…Heat shock protein 90 (Hsp90) activates eNOS, leading to NO production (18). Recently, we reported a mechanism of alcohol-driven LSEC dysfunction (19). In this study, we showed that LSECs can metabolize ethanol and that ethanol can increase Hsp90 acetylation through enhanced production of acetyl-CoA, a substrate for protein acetylation, by the action of alcohol dehydrogenase1 (ADH1) and cytochrome P450 2E1 (CYP2E1) (19).…”
Section: Capillarizationmentioning
confidence: 91%
“…Further, acetylation of Hsp90 decreases its interaction with eNOS, decreasing production of eNOS-derived NO, while a de-acetylation mutant of Hsp90 increases an interaction with eNOS, leading to NO production. Overexpression of histone deacetylase 6 (HDAC6), an Hsp90 specific de-acetylase enzyme (20), in liver endothelial cells in mice increased the association of Hsp90 with eNOS and increased NO production, resulting in ameliorating alcohol-induced liver injury (19). These observations indicate that LSEC dysfunction can be treated in an ethiology-specific manner.…”
Section: Capillarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of unsaturated PAs occurs in the hepatocytes [ 172 ] and not in the LSECs that do not express active CYP isoforms like CYP 3A4 [ 185 ], essential for PA degradation ( Table 4 ) [ 172 ]. Instead, LSECs merely express the CYP 1B1 and CYP 2E1 isoforms [ 185 , 186 , 187 ], both lack relevance for enzymatic PA degradation [ 172 ]. LSECs with their CYP 2E1 metabolize ethanol [ 187 ], and CYP 1B1 impacts the angiogenic and inflammatory properties of LSECs [ 185 ].…”
Section: The Role Of Cytochrome P450 In Metabolizing and Toxifying Unsaturated Pasmentioning
confidence: 99%
“…However, the mechanism of APAP-induced sinusoidal endothelial cell injury is still unclear. It has recently been reported that LSECs expressed CYP2E1, which is a key enzyme for metabolizing APAP into toxic intermediate NAQPI [18]. It suggests that APAP may directly induce sinusoid endothelial cell damage.…”
Section: Discussionmentioning
confidence: 99%